User Visit Certification and Visit Trace System Using Inaudible Frequency - Myoungbeom Chung (Signals, 2025)
This study proposes a user visit certification and visit trace system using inaudible frequencies in the range of audible frequencies but not those audible to people. The signal frequency consists of inaudible frequencies in the range of 18 kHz to 20 kHz, which can be generated by normal speakers. This system recognizes the signal frequency and sends signal values, users’ IDs, and location information to a server to certify the current user’s location. The server categorizes and stores the user’s visit history by individual, and the user can check their personal visit trace information in the application. To verify the utility of the proposed system, we developed an application for user certification and tracing based on a smart device and a built server system. We conducted user certification and trace experiments using the proposed system, resulting in 99.6% accuracy. As a comparative experiment, we conducted a visit certification experiment using a QR code and the proposed system and found that the proposed system performed better. Thus, the proposed system will be a useful technology for epidemiological surveys for individual users and electronic entry lists to restaurants and facilities in the age of COVID-19.